Hijamah (cupping therapy) : a comprehensive review - Shiffa, M.; Fahamiya, N.; Siddiqui, M.A.; Zaman, F. (International Journal of Universal Pharmacy and Bio Sciences, 2016)
The Unani system of medicine originated from Greece. Hippocrates is the father of medicine who initiated the humoural theory. Then Arab and Persian physicians like Rhazes, Avicenna constructed and developed this system. The aim of this study is to provide comprehensive review in cupping therapy which is now practiced effectively worldwide. This review was done by analyzing authentic Unani texts, thesis reports and published scientific journals. According to that the humoural theory which consists four humours, and proper balance of these humours ensures efficient metabolism, prevents the build-up of toxins, and maintains optimum health. Imbalance is often the root cause for origin and development of diseases. When treating such ailments, it is carried out by correcting qualitative and quantitative imbalances of humours. Hijamah is a method used to correct, evacuate or divert morbid humours in Unani medicine. According to Avicenna ‗cupping depurates and balances the humours. Thus cupping removes bad or morbid matters from the body, neutralizes the humours and helps to regain the health. Nowadays, it is being proved by various clinical trials that cupping therapy has beneficial effects on human beings. According to latest scientific interpretation, the mechanism of action most likely involves a local increase and activation of blood flow and increases the elimination of metabolites or moves them from one part to another part of body. Furthermore it activates the immune system. Therefore it removes the pathogenic factors lead to ease local symptoms and helps to regain the health.
Keywords: Hijamah; Depurates; Bad matters; Humours